A Late Jurassic plesiosaur in Antarctica: Evidence of the dispersion of marine fauna through the Trans-Erythraean Seaway? - O'gorman, Jose Patricio; Gouiric Cavalli, Soledad; Scasso, Roberto Adrian; Reguero, Marcelo Alfredo; Moly, Juan J.; Acosta-Burlaille, Leonel (Comptes Rendus Palevol)
During the Jurassic two main marine pathways might act as dispersion routes for vertebrates and invertebrates between Laurasia and Gondwana: the Caribbean Seaway (between North and South America) and the Trans-Erythraean Seaway (splitting Africa from India, Madagascar). The former has proven to be of relevance as a dispersion route for marine vertebrates and invertebrates between the Tethys and Pacific margin of Gondwana. Nevertheless, little is known about the role of the Trans-Erythraean Seaway as a vertebrate dispersion pathway. The Trans-Erythraean Seaway divides the eastern and western South of Gondwana landmasses in the so-called break-up of Gondwana and connects the Tethys Sea with the Palaeo-Pacific. We describe a newly recovered plesiosaur specimen from the Ameghino (= Nordensköld) Formation, Antarctic Peninsula, the first Jurassic plesiosaur from Antarctica. We discuss the importance of this record regarding the hypothesis of marine vertebrate dispersion through the Trans-Erythraean Seaway. Pendant le Jurassique, deux principales voies maritimes ont pu servir d’itinéraires de dispersion des vertébrés et invertébrés entre la Laurasie et le Gondwana : la mer des Caraïbes (entre l’Amérique du Nord et l’Amérique du Sud) et la voie Trans-Érythréenne séparant l’Afrique de l’Inde–Madagascar. Il a été prouvé de manière pertinente que la première a été un itinéraire de dispersion pour les vertébrés et invertébrés marins. Mais on connaît peu de chose du rôle qu’a pu jouer la Trans-Érythréenne en tant qu’itinéraire de dispersion des vertébrés. La voie Trans-Érythréenne divise les masses continentales des parties est et ouest du Sud-Gondwana en formant la fracture appelée gondwanienne, qui connecte la Téthys au Paléo-Pacifique. Nous décrivons ici un spécimen de plésiosaure nouvellement répertorié dans la formation Ameghino (= Nordensköld) de la péninsule Antarctique, le premier plésiosaure découvert en Antarctique. Nous discutons l’importance de cette découverte en ce qui concerne l’hypothèse d’une dispersion ...